Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the equation of the line that passes through the points [tex]\((-3, -1)\)[/tex] and [tex]\((3, 3)\)[/tex], we can follow these steps:
1. Calculate the Slope of the Line ([tex]\(m\)[/tex]):
The formula for the slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Using the points [tex]\((-3, -1)\)[/tex] and [tex]\((3, 3)\)[/tex], we get:
[tex]\[ m = \frac{3 - (-1)}{3 - (-3)} = \frac{3 + 1}{3 + 3} = \frac{4}{6} = \frac{2}{3} \][/tex]
2. Form the Equation in Point-Slope Form:
The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = \frac{2}{3}\)[/tex], [tex]\(x_1 = -3\)[/tex], and [tex]\(y_1 = -1\)[/tex]:
[tex]\[ y - (-1) = \frac{2}{3}(x - (-3)) \][/tex]
Simplify:
[tex]\[ y + 1 = \frac{2}{3}(x + 3) \][/tex]
3. Convert to Slope-Intercept Form ([tex]\(y = mx + b\)[/tex]):
Distribute [tex]\(\frac{2}{3}\)[/tex] and simplify:
[tex]\[ y + 1 = \frac{2}{3}x + \frac{2}{3} \cdot 3 \][/tex]
[tex]\[ y + 1 = \frac{2}{3}x + 2 \][/tex]
Subtract 1 from both sides:
[tex]\[ y = \frac{2}{3}x + 1 \][/tex]
4. Convert to Standard Form [tex]\(Ax + By = C\)[/tex]:
Multiply all terms by 3 to eliminate the fraction:
[tex]\[ 3y = 2x + 3 \][/tex]
Rearrange to get the standard form:
[tex]\[ 2x - 3y = -3 \][/tex]
So, the equation of the line that goes through [tex]\((-3, -1)\)[/tex] and [tex]\((3, 3)\)[/tex] is:
[tex]\[2x - 3y = -3\][/tex]
Therefore, the correct option is:
D. [tex]\(2x - 3y = -3\)[/tex]
1. Calculate the Slope of the Line ([tex]\(m\)[/tex]):
The formula for the slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Using the points [tex]\((-3, -1)\)[/tex] and [tex]\((3, 3)\)[/tex], we get:
[tex]\[ m = \frac{3 - (-1)}{3 - (-3)} = \frac{3 + 1}{3 + 3} = \frac{4}{6} = \frac{2}{3} \][/tex]
2. Form the Equation in Point-Slope Form:
The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = \frac{2}{3}\)[/tex], [tex]\(x_1 = -3\)[/tex], and [tex]\(y_1 = -1\)[/tex]:
[tex]\[ y - (-1) = \frac{2}{3}(x - (-3)) \][/tex]
Simplify:
[tex]\[ y + 1 = \frac{2}{3}(x + 3) \][/tex]
3. Convert to Slope-Intercept Form ([tex]\(y = mx + b\)[/tex]):
Distribute [tex]\(\frac{2}{3}\)[/tex] and simplify:
[tex]\[ y + 1 = \frac{2}{3}x + \frac{2}{3} \cdot 3 \][/tex]
[tex]\[ y + 1 = \frac{2}{3}x + 2 \][/tex]
Subtract 1 from both sides:
[tex]\[ y = \frac{2}{3}x + 1 \][/tex]
4. Convert to Standard Form [tex]\(Ax + By = C\)[/tex]:
Multiply all terms by 3 to eliminate the fraction:
[tex]\[ 3y = 2x + 3 \][/tex]
Rearrange to get the standard form:
[tex]\[ 2x - 3y = -3 \][/tex]
So, the equation of the line that goes through [tex]\((-3, -1)\)[/tex] and [tex]\((3, 3)\)[/tex] is:
[tex]\[2x - 3y = -3\][/tex]
Therefore, the correct option is:
D. [tex]\(2x - 3y = -3\)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.